Oriented cell motility and division underlie early limb bud morphogenesis - Wyngaarden, Laurie A. (Company of Biologists, 2010)
The vertebrate limb bud arises from lateral plate mesoderm and its overlying ectoderm. Despite progress regarding the genetic requirements for limb development, morphogenetic mechanisms that generate early outgrowth remain relatively undefined. We show by live imaging and lineage tracing in different vertebrate models that the lateral plate contributes mesoderm to the early limb bud through directional cell movement. The direction of cell motion, longitudinal cell axes and bias in cell division planes lie largely parallel to one another along the rostrocaudal (head-tail) axis in lateral plate mesoderm. Transition of these parameters from a rostrocaudal to a mediolateral (outward from the body wall) orientation accompanies early limb bud outgrowth. Furthermore, we provide evidence that Wnt5a acts as a chemoattractant in the emerging limb bud where it contributes to the establishment of cell polarity that is likely to underlie the oriented cell behaviours.